Directed flow from parton spin-orbit coupling in pp and pA collisions - Sanjin Benić; Yoshitaka Hatta (Physics Letters B)
We point out a novel mechanism to generate cos⁡ϕ two-particle azimuthal correlation (‘directed flow’) in unpolarized proton-proton and proton-nucleus collisions in the forward rapidity region of the projectile proton. This is a direct consequence of the recently discovered strong spin-orbit coupling in gluons at small-x. The observable simultaneously serves as a unique probe into the double helicity parton distribution functions of the proton.